2017
DOI: 10.1515/eces-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Copper Ions on Oxidative Stress in Garden Cress Lepidium sativum

Abstract: Normal oxygen metabolism is an endogenous source of reactive oxygen species (ROS). The source of ROS are also many environmental factors including heavy metals. In certain concentration range, the presence of ROS is necessary to maintain proper cell function. Thus, cells have many mechanisms, which role is focused on maintaining a constant concentration of ROS. Imbalance between the formation of ROS and action of a protective antioxidant system leads to oxidative stress. This may results with a damage to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…MDA is a widely used marker of environmental stress in plants [37]. The content of MDA and the activity of antioxidant enzymes is expected to increase initially and then decrease due to excessive Cu [38][39][40], which is consistent with our findings. Zhou et al (2015) studied the changes of physiological and biochemical reactions of forest trees under different levels of Pb stress, and showed that the activities of superoxide dismutase (SOD), peroxidase (POD) and MDA contents in trees were significantly increased under Pb stress [41].…”
Section: Discussionsupporting
confidence: 91%
“…MDA is a widely used marker of environmental stress in plants [37]. The content of MDA and the activity of antioxidant enzymes is expected to increase initially and then decrease due to excessive Cu [38][39][40], which is consistent with our findings. Zhou et al (2015) studied the changes of physiological and biochemical reactions of forest trees under different levels of Pb stress, and showed that the activities of superoxide dismutase (SOD), peroxidase (POD) and MDA contents in trees were significantly increased under Pb stress [41].…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, the antioxidant system consisting of enzymes such as superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in plants scavenges ROS to ensure normal plant growth (Shahid et al 2014). At the same time, the production of ROS also increases malondialdehyde (MDA) activity, which is positively correlated with exogenous Cd stress concentration within a certain range (Rombel-Bryzek et al 2017). In this study, leaves MDA and CAT activities increased with Cd concentration, and SOD and POD activities decreased with Cd concentration, indicating that cotton membrane system damage was increased and metabolically generated H 2 O 2 was mainly scavenged by CAT (Wu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Copper is an important environmental pollutant [ 78 ] and according to WHO, the tolerable concentrations of copper in drinking water is 2 ppm [ 79 ]. Excess levels of copper ions lead to oxidative stress, resulting in childhood cirrhosis, prion disease, Menkes disease, Parkinson's disease, and Wilson disease [ 80 ]. Similarly, the sulfide (S 2- ) anions are generated due to synthesis of sulfur and sulfuric acid, dyes, and cosmetics.…”
Section: Toxic Anionsmentioning
confidence: 99%